PENGARUH GURU DAN TEMAN SEBAYA TERHADAP PENDIDIKAN AKHLAK SISWA DI MTS NEGERI 2 KOTA BENGKULU - Febi Nina Barokah (IAIN Bengkulu, 2018)
This study to determine whether there is a significant influence of positive teachers and peers against moral education students In MTs Negeri 2 Kota Bengkulu. This research uses quantitative approach. The population is all students of class VI MTs Negeri 2 Kota Bengkulu. Sampling is done by purposive sampling that is determination technique with certain consideration. Data were analyzed by using simple and double linear regression test.The result of this research shows that there is a significant influence between teacher toward moral education of VII MTS Negeri 2 Kota Bengkulu academic year 2016/2017 is 30.7%, while the rest 69.3% is influenced by other variables besides teacher variables. There is a significant influence between peers to moral education of students is 10.3% and There is a significant influence between teachers and peers to moral education of students by 55.6% while the remaining 44.4% dipegaruhi by variables other than teacher variables and peers